External sector indicators and Kosovo's economic development: A study from 2007-2019 and during the Covid-19 pandemic - Albrim Salajdin Badallaj (Economics, Management and Sustainability)
The aim of this paper is to examine the impact of four crucial indicators on Kosovo's external sector: imports, exports, remittances, and foreign direct investment, in relation to economic development. The study draws on data from reputable domestic and foreign institutions, such as KAS, CBK, IMF, and World Bank, to ensure reliable and valid statistical analysis. The research methodology employed in this study is quantitative and comparative, using secondary data analysis, Microsoft Excel, and image analysis techniques. The results indicate that these indicators play a significant role in Kosovo's economic growth, but various political and economic factors, including crises, influence their performance. The trade deficit has increased steadily over the years, except in 2020, when there was a decrease in imports and an increase in exports due to the Covid-19 pandemic. Remittances have exhibited a linear upward trend every year, whereas foreign direct investment has declined continuously, reaching its peak in 2007 and slightly improving in 2020. The study concludes that the Covid-19 pandemic has underscored the unpredictability of these indicators during times of crisis. Consequently, Kosovo must establish tax and fiscal incentives to attract foreign direct investment, channel remittances efficiently, and promote product standardization to reduce the trade deficit.